Medicolegal cases : A Potential Source of Coronavirus (SARSCoV-2) Infection in Indian Police Personnel (Indian Journal of Forensic Medicine & Toxicology, 2020)
India accompanies the world witnessing a rapidly spreading global pandemic of Covid-19. On 24 March,the Government of India ordered a nationwide lockdown that triggered the mass migration of daily wagesworkers back to their native states. Without prior testing for SARS-CoV-2, it imposed a new challengetowards the authorities to prevent the possible spread of infection. The study aims to determine the infectionstatus of migrants who died in the jurisdiction of Varanasi district during their journey and the possible risk ofspread of Covid-19 to frontline workers. The study was conducted between 24 March 2020 and 10 July 2020.A total of 6 cases came to our department who died during travel. The nasopharyngeal and oropharyngealswabs were taken after the body arrived in the mortuary and sent for detection of SARS-CoV-2 by RT-PCRmethod to the Viral Research and Diagnostic Laboratory (VRDL), Department of Microbiology of ourInstitute. A total of six cases were included in this study, of which 3 were positive for SARS-CoV-2 whileothers were negative. None of them had symptoms of Covid-19 infection, such as respiratory difficulties,sore throat or fever. The guidelines issued by the Ministry of Health and Family Welfare were limitedin scope to hospital deaths and lacked guidelines to be followed by police personnel while investigatingunnatural deaths. This brings the police personnel at risk of contracting Covid-19 infection as the cases aregetting tested after the arrival at mortuary. The only way of protection is prevention, which mandates layingdown the guidelines at the earliest.